2019
DOI: 10.1002/solr.201900190
|View full text |Cite
|
Sign up to set email alerts
|

Carbon‐Electrode Based Perovskite Solar Cells: Effect of Bulk Engineering and Interface Engineering on the Power Conversion Properties

Abstract: Carbon electrodes have been adopted widely in perovskite solar cells (PSCs). Due to its suitable work function (though not high enough), the carbon electrode itself could extract photogenerated holes and has helped to achieve a power conversion efficiency of ≈16% in the absence of hole‐transporting material. Meanwhile, due to the inert chemical nature and the micrometer‐sized film thickness (≈10 μm), carbon electrodes can prolong the stability of PSCs. These merits are appealing for the commercialization of PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 130 publications
(254 reference statements)
0
33
0
Order By: Relevance
“…The highest PCE for planar CPSCs of 19.2% was achieved by Zhang et al Their devices retained 95% of the initial PCE after 1000 h storage in ambient condition. [269] Similarly, Yan at al. reported a storage stability of 5 months under the humidity of ≈45% RH for the planar CPSC with a PCE of 14.77%.…”
Section: Stable Nonmetal Electrodes As Barriersmentioning
confidence: 98%
“…The highest PCE for planar CPSCs of 19.2% was achieved by Zhang et al Their devices retained 95% of the initial PCE after 1000 h storage in ambient condition. [269] Similarly, Yan at al. reported a storage stability of 5 months under the humidity of ≈45% RH for the planar CPSC with a PCE of 14.77%.…”
Section: Stable Nonmetal Electrodes As Barriersmentioning
confidence: 98%
“…On the other hand, it was reported that gold and silver may adversely affect the performance due to the presence of halogen atom resulting in the undesirable formation of their respective halides [175][176][177][178]. For those reasons, carbon-based electrode materials [graphite, carbon black, graphene and carbon nanotubes (CNTs)] for various device geometries (mesoscopic, planar, and quasi-planar) are given primary importance toward cheaper, stable and large-scale processable F-PSCs [174,179,180]. It is worth highlighting a few of the highly resilient, lowtemperature processable, conductive hybrid carbon-based printable electrodes that are equally comparable to F-PSCs [181,182].…”
Section: Role Of Flexible Contact Electrodesmentioning
confidence: 99%
“…2) The stability concerns are tackled using the ultrathick CE with a thickness of over 10 μm, which exceptionally diminishes the H 2 O/O 2 penetration that persuades halide corrosion and perovskite degradation. [ 182 ] 3) The overall cost of the device is effectively reduced with the use of low‐cost CEs. 4) The current conduction and hole extraction is efficiently enhanced, which increase the PCE of PSC.…”
Section: Cspbi2br Pscsmentioning
confidence: 99%